A four-seat light airplane design - Muhamad, Sallehuddin; Hamid, Khairul Azura (2003)
Malaysia produces two-seat light airplane through two firms, SME Aerospace Sdn. Bhd. and Eagle Aircraft Sdn. Bhd. As these airplanes are limited to recreational, flight training and acrobatic activities, a four-seat airplane was proposed. Financed by the Ministry of Science and Technology, a research team was formed. The new airplane was designed based on the SME two-seat airplane, the MD3-160 using Professor Jan Roskam methodology. In the process, AutoCAD® and General Aviation Computer Aided Design® software were utilized. Preliminary results indicated that the designed four-seat airplane has better performance than the original two-seat airplane and at the same time staying very competitive in comparison to others in its class. The airplane also is very stable and possessing the Level 1 flying qualities.